Need for cognition, academic self-efficacy and parental education predict the intention to go to college—evidence from a multigroup study - Lina Kramer; Stefanie Lüdtke; Philipp Alexander Freund (Frontiers in Psychology)
Academic success is not solely the result of cognitive ability. There is evidence that traits such as students' need for cognition (NFC) and self-efficacy beliefs influence academic success. Beyond cognitive ability and personal traits, social background constitutes an important factor. Students from academic households are (still) much more likely to pursue an academic degree than their peers from non-academic households. Past research on traits and beliefs relevant in (higher) education has focused on academic success, but only to a limited extent on its direct precursor: the decision to pursue an academic degree. This study aims to investigate NFC and academic self-efficacy (ASE) as positive predictors of students' intentions to go to college, with consideration of students' generational status regarding academic education. Results based on survey data from 1,389 German high school students provide evidence for positive relationships between NFC, ASE, and study intention, with ASE acting as a mediator of NFC's effect. Our analyses also investigate the effects of NFC and ASE on study intentions for students from academic as compared to students from non-academic households via multigroup analyses.